Increased risk of humerus and lower leg fractures in postmenopausal women with self-reported premenopausal hirsutism and/or oligomenorrhea. (August 2016) - Comim, Fabio V.; Marchesan, Luana Q.; Copes, Rafaela M.; de Vieira, Adhan R.; Moresco, Rafael N.; Compston, Juliet E.; Premaor, Melissa O.
Abstract: Objective: The aim of this study was to investigate the prevalence of fracture in women aged >55 years with self-reported premenopausal hirsutism and/or oligomenorrhea. Study design: A cross-sectional study including 1057 post-menopausal women aged >55 years who were treated in a primary care facility in Santa Maria, South Brazil, from March 2013 through August 2013. Data were collected using a standardized questionnaire for characteristics including fracture history, medication use, and reproductive history (oligomenorrhea, hirsutism, miscarriage, the diagnosis or treatment of hypothyroidism, hyperprolactinemia, or infertility). Results: A non-significant trend towards an increased prevalence of all fragility fractures was observed in women with premenopausal hirsutism and/or oligomenorrhea when compared to those without (20.4% vs. 15.7%). After correction for age, falls, and comorbidities, fracture prevalence was significantly higher in the lower leg (OR 3.1 [CI 1.1–8.6]; P  = 0.029), and humerus (OR 2.6 [CI 1.2–5.4]; P  = 0.015) in the women with hirsutism and/or oligomenorrhea. Conclusion: This is a hypothesis-generating study which evaluated the association between hirsutism and/or oligomenorrhea and fractures in postmenopausal women. Our results suggest that premenopausal hirsutism and/or oligomenorrhea may be associated with an increased risk of fracture postmenopause, particularly in the humerus and lower leg.